(In)equality of opportunity in education and the mechanism of non-reproduction - Burak O. S. (Український соціум, 2020)
In this article we would like to discuss, based on the results of empirical studies, the question of monopoly position of educational institutions in the distribution of life chances and the factors that could promote social mobility. The main theoretical focus is on the theory of reproduction and on the new theoretical perspective of non-reproduction. Frequently it is precisely the education system itself, the one that inhibits upward social mobility and serves to preserve and reproduce the existing social order with its inequalities. A child’s path throughout the school can be strongly influenced by its class of origin. This principle underlies the theory of reproduction. However, the theory shows its “blind spots”, this is, when a child doesn’t reproduce its own class and successes an upward transition from the lower class to the higher one. Chantal Jaquet names this process a non-reproduction and tries to work out a theory that could explain how a child can transform itself and avoids falling back into the behavior of its class of origin. From this point of view, some exceptional cases can serve as an excellent observatory to determine the decisive factors of an effective change. That is why we decided to look at a few life stories of “class crosses” in depth, using qualitative methods of analysis. The “class crossers” of our study were students from some middle schools (NMS) in Vienna, who could go to the grammar school (Gymnasium). Our aim was to empirically test some statements of the reproduction theory and of the new non-reproduction theory. For this purpose, we tried to reconstruct those factors, that could explain the success of the “class crossers”. Five cases of transition were analyzed and, as a result, some institutional factors that make it difficult for young people to get to and through the gymnasium were identified. Besides, it was proved that adolescents must deal with them mostly on their own using the resources of the family and activating their personal set of mental and physical skills that Jaquet names “complexion”. Moreover, some perspectives for further research opened up: the choice of profession that could lead to social upward mobility, the role of gender of the students and the educational level of their parents on the school path.